'Many pieces one family': An elaboration of one family's bereavement experiences. Issue 1 (13th January 2022) - Gaussen, Kathryn; Stedmon, Jacqui; Smart, Cordet
There has been considerable research on bereavement and the concept of continuing bonds. However, there is a distinct absence of research considering bereavement, continuing bonds and family dynamics post-bereavement. The paper reports on a study utilising a family systems approach combined with narrative methods, tools of conversation analysis and systemic theory. This integration of approaches is used to consider how one family offers an account of their experience of bereavement. An exploration of their conversation along with visual presentation in the form of button sculpts is employed. The findings support the suggestion that it is useful to consider bereavement experiences as part of a family system. Clinical implications of the research are outlined to consider how best to support bereaved families.